2003
DOI: 10.1002/mats.200350003
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of the Polymerization‐Induced Phase Separation Phenomenon in Polymer Solutions under a Temperature Gradient

Abstract: This paper studied the polymerization‐induced phase separation phenomenon (spinodal decomposition) in a model binary polymer solution under a linear spatial temperature gradient for the purpose of fabricating anisotropic polymeric materials by using mathematical modeling and computer simulation. Reaction kinetics were incorporated with the non‐linear Cahn‐Hilliard theory and the Flory‐Huggins free energy expression in the model. Moreover, the slow mode theory and Rouse law were used to account for polymer diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…2(a 0 ), 2(b 0 ), and 2(c 0 ) ] with otherwise identical parameters by setting D T 0 in Eq. (7). All other parameters of the model were kept constant and the same initial conditions were used [ Fig.…”
Section: (C)] and Moves Away From The Central Spot Like A Spherical Wmentioning
confidence: 99%
See 1 more Smart Citation
“…2(a 0 ), 2(b 0 ), and 2(c 0 ) ] with otherwise identical parameters by setting D T 0 in Eq. (7). All other parameters of the model were kept constant and the same initial conditions were used [ Fig.…”
Section: (C)] and Moves Away From The Central Spot Like A Spherical Wmentioning
confidence: 99%
“…Yamamura et al [4] observed the formation of stripe patterns in demixing fluids caused by thermocapillary flow and Okinaka et al [5] describe directional phase separation of a polymer blend driven by a temperature gradient. Lee et al [6,7] performed a computational study on the spinodal decomposition process within a temperature gradient. Spatially periodic patterns formed after driving a binary polymer mixture periodically above and below the instability [8].…”
mentioning
confidence: 99%
“…For instance, the permeability, throughput, and cleanability improve significantly for a polymer membrane with anisotropic pore size 7–10. Structural morphology can be influenced by imposing an external fluctuation, such as an electric field,11, 12 concentration gradient,13, 14 shear flow,15 or temperature gradient 16–18. For instance, Lee et al16–18 simulated a phase separation phenomenon via spinodal decomposition under a spatial temperature gradient (off‐critical quench) for both thermal‐induced and polymerization‐induced phase separation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal static and dynamical properties of polymer blends or solutions have been all well established; [27,28] however, there have been few experimental [29][30][31][32] or numerical studies [21,22] reported in the literature on the phase-separating polymer solutions and/or polymer blends under the influence of an externally applied…”
Section: Introductionmentioning
confidence: 99%